The Impact of Duolingo Application on the Seventh-Grade Students’ Vocabulary Mastery - Risky, Amelya; Syafi'i S, M. (Indonesian Journal of Integrated English Language Teaching, 2023)
The goal of this study was to gather empirical data and examine how the Duolingo application was used by the seventh-grade students at MTSN 4 Rokan Hulu to increase their vocabulary mastery. The students were participated in a quasi-experimental research design and were divided into two groups, the experimental group and the control group. 131 students made up the entire population, and purposive sampling was used to obtain the sample. As a result, VII B served as the control class and VII A as the experimental class. There were 32 students in the experimental class and 30 in the control group. Vocabulary mastery test and observations were served as the data collecting tools. The test was administered twice. By using a significance level of 0.05, the data analysis findings indicate that the value of t-table was 3.476. It is greater than the value of t-table, which is 1.671. In conclusion, using the Duolingo application to improve the seventh-grade students’ vocabulary mastery at the school had a substantial impact.